Huang Di Nei Jing Su Wen : An Annotated Translation of Huang Di's Inner Classic - Basic Questions: 2 volumes - Zheng, Jinsheng, 1946-; Tessenow, Hermann, 1945-; Unschuld, Paul U. (Paul Ulrich), 1943- (Book collections on Project MUSE., 2011)
A foundation of Chinese life sciences and medicine, the Huang Di Nei Jing Su Wen is now available for the first time in a complete, fully annotated English translation. Also known as Su Wen, or The Yellow Emperor's Inner Classic, this influential work came into being over a long period reaching from the 2nd century bce to the 8th century ce. Combining the views of different schools, it relies exclusively on natural law as conceptualized in yin/yang and Five Agents doctrines to define health and disease, and repeatedly emphasizes personal responsibility for the length and quality of one's life.